STIL overexpression shortens lifespan and reduces tumor formation in mice - Moussa, Amira-Talaat; Cosenza, Marco R.; Wohlfromm, Timothy; Brobeil, Katharina; Hill, Anthony; Patrizi, Annarita; Müller-Decker, Karin; Holland-Letz, Tim; Jauch, Anna; Kraft, Bianca; Krämer, Alwin (PLoS Genetics, 2024)
Centrosomes are the major microtubule organizing centers of animal cells. Supernumerary centrosomes are a common feature of human tumors and associated with karyotype abnormalities and aggressive disease, but whether they are cause or consequence of cancer remains controversial. Here, we analyzed the consequences of centrosome amplification by generating transgenic mice in which centrosome numbers can be increased by overexpression of the structural centrosome protein STIL. We show that STIL overexpression induces centrosome amplification and aneuploidy, leading to senescence, apoptosis, and impaired proliferation in mouse embryonic fibroblasts, and microcephaly with increased perinatal lethality and shortened lifespan in mice. Importantly, both overall tumor formation in mice with constitutive, global STIL overexpression and chemical skin carcinogenesis in animals with inducible, skin-specific STIL overexpression were reduced, an effect that was not rescued by concomitant interference with p53 function. These results suggest that supernumerary centrosomes impair proliferation in vitro as well as in vivo, resulting in reduced lifespan and delayed spontaneous as well as carcinogen-induced tumor formation.
Gesehen am 06.06.2025